The effects of using collaborative learning activities on EFL young learners' vocabulary retention - Nguyễn Thị Mỹ Thương (Trường Đại học Trà Vinh, 2023)
The objectives of the research are to help EFL young learners improve vocabulary learning and vocabulary retention in the long time and to foster their positive attitude through collaborative learning activities.